2022
DOI: 10.3389/fphys.2022.1017948
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in virus-induced volatiles in cotton modulate the orientation and oviposition behavior of the whitefly Bemisia tabaci

Abstract: Manipulation of insect vector behavior by virus-induced plant volatiles is well known. But how the viral disease progression alters the plant volatiles and its effect on vector behavior remains less explored. Our studies tracked changes in volatile profile in progressive infection stages of cotton leaf curl virus (CLCuV) infected plants and their effect on B. tabaci behavior. Significant differences in virus titers were noticed between progressive infection stages showing distinct symptoms. Whiteflies initiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Does the stimulation of VOC emission by mycoviruses possess an ecological function? Plant viruses modulate the attractiveness of their hosts to animal vectors, increasing their chance of propagation [ 58 , 59 ]. The dissemination of mycoviruses by fungivores has been demonstrated in a single case [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Does the stimulation of VOC emission by mycoviruses possess an ecological function? Plant viruses modulate the attractiveness of their hosts to animal vectors, increasing their chance of propagation [ 58 , 59 ]. The dissemination of mycoviruses by fungivores has been demonstrated in a single case [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in concordance with the findings of He et al 14 who reported that these compounds enhance whiteflies’ ability to locate host plants. Furthermore, α-pinene had been implicated in eliciting a positive response from virus-infested plants to B. tabaci facilitating the rapid transmission of cucumber mosaic virus 47 , tomato leaf curl virus 48 and cotton leaf curl virus 49 . Myrcene bound strongly to both OBP8 and CSP4 (− 4.8 kcal/mol), while β-ocimene showed moderate affinities to OBP8 (− 4.8 kcal/mol) and CSP4 (− 4.3 kcal/mol).…”
Section: Discussionmentioning
confidence: 99%
“…Plants infected with a virus are preferred by the insect vector over healthy plants. This preference/early attraction relates to a combination of disease symptomatology (for example, yellowing of the leaves attracts insects) and changed volatile emission spectra [ 72 ]. Then, viruliferous insect vectors prefer healthy plants over virus-infected plants.…”
Section: Crosstalk Between Virus and Insect Transmission Vector: Anti...mentioning
confidence: 99%